The influence of access to eReaders, computers and mobile phones on children's book reading frequency - Merga, Margaret; Mat Roni, S. (Pergamon, 2017)
Regular recreational book reading is a practice that confers substantial educative benefit. However, not all book types may be equally beneficial, with paper book reading more strongly associated with literacy benefit than screen-based reading at this stage, and a paucity of research in this area. While children in developed countries are gaining ever-increasing levels of access to devices at home, relatively little is known about the influence of access to devices with eReading capability, such as Kindles, iPads, computers and mobile phones, on young children's reading behaviours, and the extent to which these devices are used for reading purposes when access is available. Young people are gaining increasing access to devices through school-promoted programs; parents face aggressive marketing to stay abreast of educational technologies at home; and schools and libraries are increasingly their eBook collections, often at the expense of paper book collections. Data from the 997 children who participated in the 2016 Western Australian Study in Children's Book Reading were analysed to determine children's level of access to devices with eReading capability, and their frequency of use of these devices in relation to their recreational book reading frequency. Respondents were found to generally underutilise devices for reading purposes, even when they were daily book readers. In addition, access to mobile phones was associated with reading infrequency. It was also found that reading frequency was less when children had access to a greater range of these devices.